LOVE AND STRUGGLE OF THE MAIN CHARACTER AS REFLECTED IN CHARLES DICKEN’S GREAT EXPECTATIONS NOVEL: A PSYCHOLOGICAL STUDY - Fahrunnisa Fahrunnisa; Hikmah Pravitasari (La Tansa Mashiro, 2021)
This paper discusses the novel